High-Wattage Pulsed Irradiation of Linearly Polarized Near-Infrared Light to Stellate Ganglion Area for Burning Mouth Syndrome - Momota, Yukihiro (Hindawi Publishing Corporation, 2014)
The purpose of this study was to apply high-wattage pulsed irradiation of linearly polarized near-infrared light to the stellate ganglion area for burning mouth syndrome (BMS) and to assess the efficacy of the stellate ganglion area irradiation (SGR) on BMS using differential time-/frequency-domain parameters (D parameters). Three patients with BMS received high-wattage pulsed SGR; the response to SGR was evaluated by visual analogue scale (VAS) representing the intensity of glossalgia and D parameters used in heart rate variability analysis. High-wattage pulsed SGR significantly decreased the mean value of VAS in all cases without any adverse event such as thermal injury. D parameters mostly correlated with clinical condition of BMS. High-wattage pulsed SGR was safe and effective for the treatment of BMS; D parameters are useful for assessing efficacy of SGR on BMS.